2021
DOI: 10.1155/2021/9954909
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Agonist of Retinoid-Related Orphan Receptor-Alpha Prevents Apoptosis and Degeneration in Nucleus Pulposus Cells via Upregulation of YAP

Abstract: Intervertebral disc degenerative disease (IDD) is the most common degenerative spine disease, which leads to chronic low back pain and symptoms in the lower extremities. In this study, we found that RORα, a member of the retinoid-related orphan receptor family, is significantly elevated in nucleus pulposus tissue in IDD patients. The elevation of RORα is associated with increased apoptosis of nucleus pulposus (NP) cells. Therefore, we applicated a well-established inverse agonist of RORα, SR3335, to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The homozygous (sg/sg) mice exhibit cerebellar ataxia, bone mineral content loss, and osteopenic phenotype [8,9]. Our studies suggested RORα regulates nucleus pulposus matrix metabolism and apoptosis [10]. Moreover, RORα contributes to chondrocyte hypertrophy during the development of endochondral bone and growth plates, acting as a prehypertrophic marker [11,12].…”
Section: Introductionmentioning
confidence: 75%
“…The homozygous (sg/sg) mice exhibit cerebellar ataxia, bone mineral content loss, and osteopenic phenotype [8,9]. Our studies suggested RORα regulates nucleus pulposus matrix metabolism and apoptosis [10]. Moreover, RORα contributes to chondrocyte hypertrophy during the development of endochondral bone and growth plates, acting as a prehypertrophic marker [11,12].…”
Section: Introductionmentioning
confidence: 75%
“…Ample studies have shown that the Hippo signaling pathway is related closely to mechanical stress and is involved in bone and cartilage degenerative diseases [ 42 , 43 ]. According to the available evidence, the YAP protein has been reported to promote the anabolic metabolism of ECM in NPCs [ 31 , 32 ]. CTGF, as the target molecule of the Hippo signaling pathway, has been reported to be involved in the ECM metabolism of nucleus pulposus cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the available evidence, the YAP protein has been reported to promote the anabolic metabolism of ECM in NPCs [ 31 , 32 ]. CTGF, as the target molecule of the Hippo signaling pathway, has been reported to be involved in the ECM metabolism of nucleus pulposus cells [ 31 , 32 ]. Nevertheless, the mechanisms governing LATS/YAP/CTGF in the regulation of NPCs have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, nucleus pulposus cells have recently been extensively investigated in LBP-W given their roles in IVD inflammation and degeneration. [50][51][52] The current bibliometric analysis identifies several research priorities. First, as a prevalent and disabling back condition, lumbar spinal stenosis (LSS) was one of the emerging trends in LBP-O research.…”
mentioning
confidence: 99%